Предмет: Алгебра, автор: Аноним

Вычислите выражения ​

Приложения:

Ответы

Автор ответа: Miroslava227
0

Ответ:

 \frac{ {2}^{ - 6} \times  {4}^{ - 3}  }{ {8}^{ - 7} }  =  \frac{ {2}^{ - 6} \times  {( {2}^{2} )}^{ - 3}  }{ {( {2}^{3} )}^{ - 7} }  =  \\  =  \frac{2 {}^{ - 6} \times  {2}^{ - 6}  }{ {2}^{ - 21} }  =   {2}^{ - 6 - 6 - ( - 21)}  =  \\  =  2^{ - 12 + 21 }  =  {2}^{9}  = 512

Автор ответа: Аноним
0

Ответ:

512

Объяснение:

 \frac{2 {}^{ - 6} \times 4 {}^{ - 3}  }{8 {}^{ - 7} }  =  \frac{2 {}^{ - 6} \times 2 {}^{ - 6}  }{2 {}^{ - 21} }  = 2 {}^{15}  \times 2 {}^{ - 6}  = 2 {}^{9}  = 512

Похожие вопросы
Предмет: Математика, автор: nika12317